The role of chloroplasts in the oxidative stress that is induced by zearalenone in wheat plants - The functions of 24-epibrassinolide and selenium in the protective mechanisms - Filek, Maria; Sieprawska, Apolonia; Kościelniak, Janusz; Oklestkova, Jana; Jurczyk, Barbara; Telk, Anna; Biesaga-Kościelniak, Jolanta; Janeczko, Anna (Plant physiology and biochemistry, 2019)
This study focused on the idea that the toxic effect of zearalenone (ZEA) and the protective actions of the brassinosteroid - 24-epibrassinolide (EBR) as well as selenium are dependent on its accumulation in chloroplasts to a high degree. These organelles were isolated from the leaves of oxidative stress-sensitive and stress-tolerant wheat cultivars that had been grown from grains that had been incubated in a solution of ZEA (30 μM), Na2SeO4 (Se, 10 μM), EBR (0.1 μM) or in a mixture of ZEA with Se or EBR. Ultra-high performance liquid chromatography techniques indicated that ZEA was adsorbed in higher amounts in the chloroplasts in the sensitive rather than tolerant cultivar. Although the brassinosteroids and Se were also accumulated in the chloroplasts, higher levels were only found in the tolerant cultivar. The application of EBR increased the homocastasterone content, especially in the chloroplasts of the tolerant plant and after the addition of ZEA. The presence of both protectants caused a decrease in the ZEA content in studied organelles and resulted in diminishing of the oxidative stress (i.e. changes in the activity of the antioxidative enzymes). Moreover, a recovery of photosystem II and decrease in the negative impact of ZEN on Hsp90 transcript accumulation was observed in plants.
Keywords: chlorofyl a; Hsp90; Enzymes; Triticum; Antioxidants; selen; oxidační stres; Brassinosteroids; HSP90 Heat-Shock Proteins; Oxidative Stress; Plant Proteins; Zearalenone; Photosynthesis; Chloroplasts; zearalenon; Carotenoids; steroidy heterocyklické; rostlinné proteiny; chloroplasty; proteiny tepelného šoku HSP90; Steroids, Heterocyclic; Selenium; antioxidancia; Wheat; Chlorophyll A; pšenice; enzymy; karotenoidy; brassinosteroidy